Systematic Mapping of Computational Tools for Studying Human-Computer Interaction - Boas, Ivan Leoni Vilas; Carvalho, Luiz Olmes; Lima, Phyllipe; Borges, Simone de Sousa; Seabra, Rodrigo Duarte (RENOTE, 2025)
The systematic mapping in this research identified 18 computer tools developed for studying topics related to human-computer interaction (HCI), most of them focused on teaching design processes through case studies. The research analyzes the characteristics, objectives, and functionalities of the identified tools. The main contribution of the article is understanding the state of the art in developing computer tools for studying HCI, creating the opportunity for future research into alternative ways of using resources for that purpose. The results revealed the identification of few currently accessible tools for collaborating with the study of HCI.